Penerapan Strategi Pembelajaran Motivasional Attention Relevance Confidence Satisfication (ARCS) untuk Meningkatkan Motivasi dan Hasil Belajar - Nur Najama; Punaji Setyosari; Munzil Munzil (Graduate School of Universitas Negeri Malang, 2020)
Abstract: This action research was conducted to improve learning motivation and learning outcomes in the fourth-grade students. The study was conducted in two cycles. Based on research in the first cycle showed that: (1) In the observation of implementation the learning by teachers reached 76% (2) the result of the motivation questionnaire reached the number of 73%. (3) The students test at 64%. The data on the cycle I have not achieved the criteria for the successful action yet. So, it was necessary to carry out improvements to the next action, namely cycle II. In the cycle II, it showed that (1) In the observation of implementation, the learning by teachers reached 88. (2) the result of the motivation questionnaire reached the number of 89%. (3) The students test results at 93%. The results of data analysis in cycle II have shown that the success criteria have been reached, so there was no need to continue the next cycle.Abstrak: Penelitian tindakan ini bertujuan untuk meningkatkan motivasi belajar dan hasil belajar siswa kelas IV. Penelitian dilaksanakan dua siklus. Berdasarkan penelitian siklus I menunjukkan bahwa (1) keterlaksanaan pembelajaran oleh guru mencapai 76%, (2) hasil angket motivasi siswa mencapai 73%, dan (3) tes hasil belajar siswa sebesar 64%. Data pada siklus I tersebut belum mencapai kriteria keberhasilan tindakan, sehingga perlu dilaksanakan perbaikan pada tindakan selanjutnya, yaitu siklus II. Pada siklus II menunjukkan bahwa (1) keterlaksanaan pembelajaran oleh guru mencapai 88%, (2) hasil angket motivasi siswa mencapai 89%, dan (3) tes hasil belajar siswa sebesar 93%. Hasil analisis data pada siklus II tersebut menunjukkan bahwa kriteria keberhasilan telah tercapai sehingga tidak perlu dilanjutkan pada siklus selanjutnya.